German volume training - Poliquin, C.
Supersets and tri-sets allow you to perform a lot of work in a short period of time. The rest-pause method allows you to use heavier weights, so you can recruit the higher threshold muscle fibers, and eccentric training enables you to overcome strength plateaus. The bottom line is that almost any training method will work (provided you do it with intensity!), at least for the few weeks it takes for your body to adapt to it. There is, however, one training system that stands above all the rest. It's brutally hard, but I've found it to be a very effective way to pack on muscle fast! In strength-coaching circles, this method is often called the "ten sets method." Because it has its roots in German-speaking countries, I like to call it German Volume Training. To the best of my knowledge, this training system originated in Germany in the mid-'70's and was popularized by Rolf Feser, who was then the National Coach of Weightlifting. A similar protocol was promoted by Vince Gironda in the U.S., but regardless of who actually invented it, it works. In Germany, the ten-sets method was used in the off-season to help weightlifters gain lean body mass. It was so efficient that lifters routinely moved up a full weight class within 12 weeks. It was the base program of Canadian weightlifter Jacques Demers, Silver Medalist in the Los Angeles Olympic Games. Jacques was known in weightlifting circles for his massive thighs, and he gives credit to the German method for achieving such a spectacular level of hypertrophy. The same method was also used by Bev Francis in her early days of bodybuilding to pack on muscle. The program works because it targets a group of motor units, exposing them to an extensive volume of repeated efforts, specifically, 10 sets of a single exercise. The body adapts to the extraordinary stress by hypertrophying the targeted fibers. To say this program adds muscle fast is probably an understatement. Gains of ten pounds or more in six weeks are not uncommon, even in experienced lifters!